Patellar tendon mechanical properties in elite jumping athletes: A prospective study - Gupta, A.; Purdam, C.; Cook, J.; Allison, G. (Journal of Science and Medicine in Sport, 2011)
Introduction: The purpose of this research was to evaluate the mechanical characteristics of the patellar tendon (PT) in elite level jumping athletes. Patellar tendon (PT) mechanical properties including strain, stiffness, stress, elastic modulus, cross-sectional area (CSA) and mechanical work done were measured a mean of 344 days, range 254-512, apart.